Does Religiosity Explain Cross-National Differences in Crime?: The Case of American Versus Malaysian University Students - Hoskin, Anthony W. (The journal of religion & society, 2017)
Based on self-report data of college students from Malaysia (N = 1,359) and the United States (N = 1,629), crime rates of the two samples are compared. Criminal behavior is much more common in the American sample despite the country’s greater wealth. Negative binomial regression analysis reveals that the lower alcohol consumption and especially the greater religiosity of the Malaysian students help explain their lower crime rate. Theoretical implications, study limitations, and avenues for future research are discussed.